Analisis Eductive Punishment dalam Mendorong Prestasi Akademik Santri: Educative Punishment, Prestasi Akademik Santri - Faizi Nisa; Afif Al Farobi; Ayu Rahmawati (Inisiasi : Jurnal Manajemen Pendidikan Islam, 2025)
Discussing students' academic achievement is inevitably linked to their upbringing while receiving an education at their Islamic boarding school (pondok pesantren). Learning achievements are typically derived from formal and non-formal education. However, Al Mardliyyah Islamic Boarding School in Demangan, Madiun City, employs a unique strategy to support its students' academic achievement: the implementation of educative punishment. This research uses a descriptive qualitative method. The informants in this study were the head of the boarding school, a female teacher (ustadzah), security personnel, administrative staff, and student representatives. Data were collected through observation, interviews, and documentation. The analysis technique involved data collection, data condensation, data display, and conclusion drawing/verification. Data validity was checked using triangulation techniques. The results show that the implementation of educative punishment at Al Mardliyyah Islamic Boarding School in Demangan Taman, Madiun City, emphasizes constructive learning and character development, devoid of physical or mental violence. The application of this punishment also supports students' academic achievement through learning facilities and a structured daily schedule, which ultimately fosters discipline and responsibility in their formal education. Despite facing several obstacles, such as changes in management, the diverse characters of the students, and a lack of understanding from parents and the community, educative punishment remains effective when applied consistently, communicatively, and wisely in accordance with Islamic values.